2019
DOI: 10.1080/09546634.2019.1682503
|View full text |Cite
|
Sign up to set email alerts
|

Real-life experience on effectiveness and safety of dupilumab in adult patients with moderate-to-severe atopic dermatitis

Abstract: Sandoz and Sanofi. A. Cristaudo has been principal investigator in clinical trials sponsored by Abbvie, Leo Pharma and Pfizer. F. Cusano received honoraria as speaker and advisory board member from Sanofi Genzyme. M. Esposito has served as a speaker for Sanofi-Genzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 21 publications
(37 reference statements)
10
62
1
7
Order By: Relevance
“…Dupilumab, a monoclonal antibody against interleukin-4 receptor alpha, has been used in numerous allergic diseases and works by blocking signaling of interleukin-4 and interleukin-13, type 2/Th2 cytokines. It has been confirmed to be effective in patients with moderate to severe AD in several double-blind, placebocontrolled studies and in clinical practice [43][44][45]. The result showed that clinical improvement is positively correlated with increased favorable microbial community and reduced abundance of S. aureus [46].…”
Section: Biological Therapy In Patients With Admentioning
confidence: 90%
“…Dupilumab, a monoclonal antibody against interleukin-4 receptor alpha, has been used in numerous allergic diseases and works by blocking signaling of interleukin-4 and interleukin-13, type 2/Th2 cytokines. It has been confirmed to be effective in patients with moderate to severe AD in several double-blind, placebocontrolled studies and in clinical practice [43][44][45]. The result showed that clinical improvement is positively correlated with increased favorable microbial community and reduced abundance of S. aureus [46].…”
Section: Biological Therapy In Patients With Admentioning
confidence: 90%
“…Dupilumab has been demonstrated to be an effective treatment for patients with moderateto-severe AD in clinical trials [9][10][11] and in real-life studies [2,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. To date, there have been some reports on real-world experience with dupilumab, including six multicenter studies [14,19,[22][23][24]26].…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 5 ] Excellent therapeutic success of the anti-interleukin 4 receptor-α antibody dupilumab in clinical trials and in a real-world clinical context has indicated the crucial roles of T helper type 2 (Th2) cytokines, interleukin (IL)-4 and IL-13, in the pathogenesis of AD. [ 6 8 ] Along with the clinical improvement in skin scores and pruritus, dupilumab significantly and progressively reduces and normalizes the elevated expression of Th2 signatures such as Chemokine (C-C motif) ligand (CCL)17, CCL18, CCL22, and CCL26 in the lesional skin of AD. [ 9 , 10 ] Other lesional and blood markers including eosinophils, [ 11 13 ] lactate dehydrogenase (LDH), [ 14 ] total immunoglobulin E (IgE), [ 15 ] soluble IL-2 receptor, [ 16 ] CCL27, [ 14 ] IL-13, [ 17 ] IL-22, [ 9 ] IL-24, [ 18 , 19 ] IL-25, [ 20 ] IL-31, [ 21 , 22 ] IL-33, [ 23 ] thymic stromal lymphopoietin (TSLP), [ 24 ] periostin, [ 9 , 25 ] and squamous cell carcinoma antigen-2 (SCCA2) [ 26 , 27 ] are elevated in AD and show substantial correlations with its disease activity.…”
Section: Introductionmentioning
confidence: 99%